Application of Profile Matching in Employee Recruitment (Case Study of CV. Tira Gemilang) - Ayu Nuriana Sebayang (Institute of Computer Science (IOCS), 2021)
Recruitment is a process of hiring employees who will be placed in one position to carry out certain activities. Generally, the recruitment or hiring of employees has techniques or methods in the appraisal process. Such as the stage of the entrance test or in-person interviews conducted by a psychologist appointed by the company. So in general, the recruitment system is applied manually but the indicators have been determined. The process that occurs takes a lot of time, sometimes in an assessment using feelings, this assessment should be carried out objectively. For this reason, a decision support system for company recruitment was built using the profile matching method. This method is suitable for carrying out the recruitment process based on near-perfect criteria.